Long-read sequencing resolves a complex structural variant in PRKN Parkinson's disease - Daida, Kensuke; Funayama, Manabu; Billingsley, Kimberley J; Malik, Laksh; Miano-Burkhardt, Abigail; Leonard, Hampton L; Makarious, Mary B; Iwaki, Hirotaka; Ding, Jinhui; Gibbs, J Raphael; Ishiguro, Mayu; Yoshino, Hiroyo; et al. (medRxiv : the preprint server for health sciences, 2023)
mutations are the most common cause of young onset and autosomal recessive Parkinson's disease (PD). is located in FRA6E which is one of the common fragile sites in the human genome, making this region prone to structural variants. However, complex structural variants such as inversions of are seldom reported, suggesting that there are potentially unrevealed complex pathogenic structural variants. To identify complex structural variants in using long-read sequencing. We investigated the genetic cause of monozygotic twins presenting with a young onset dystonia-parkinsonism using targeted sequencing, whole exome sequencing, multiple ligation probe amplification, and long-read. We assessed the presence and frequency of complex inversions overlapping using whole-genome sequencing data of AMP-PD and UK-Biobank datasets. Multiple ligation probe amplification identified a heterozygous exon 3 deletion in and long-read sequencing identified a large novel inversion spanning over 7Mb, including a large part of the coding DNA sequence of . We could diagnose the affected subjects as compound heterozygous carriers of . We analyzed whole genome sequencing data of 43,538 participants of the UK-Biobank and 4,941 participants of the AMP-PD datasets. Nine inversions in the UK-Biobank and two in AMP PD were identified and were considered potentially damaging and likely to affect isoforms. This is the first report describing a large 7Mb inversion involving breakpoints outside of . This study highlights the importance of using long-read whole genome sequencing for structural variant analysis in unresolved young-onset PD cases.